Perceived Neighborhood Social Environment and Adolescent Depressive Symptoms: Insights from the Add Health - Rachel J. Kulchar; Breanna J. Rogers; Sam J. Neally; Alyssa Shishkov; Yangyang Deng; Mohammad Moniruzzaman; Kosuke Tamura (Health Equity)
Introduction: Adolescents experience major depression at disproportionately higher rates than their adult counterparts. Perceived neighborhood social environment (PNSE) has been linked with depressive symptoms among adolescents. The primary aim was to investigate the relationships between each PNSE and depressive symptoms. The secondary aim was to examine whether these associations may be varied by gender and race/ethnicity. Methods: Participants (n = 6083; mean age = 15.4) from the 1994–1995 National Longitudinal Study of Adolescent to Adult Health (Add Health) were asked to respond to items on depressive symptoms using the Center for Epidemiologic Studies Depression Scale (CES-D) and perceived neighborhood measures. The two depressive symptoms outcomes based on CES-D score were a continuous CES-D score and a three-level depressive symptoms variable: (i) minimal symptoms score (referent) <16, (ii) mild: 16 ≤ CES-D < 24, and (iii) moderate/severe: CES-D ≥24. PNSE included safety, social cohesion, and contentedness (i.e., 1-standard deviation unit increase). Weighted regression models were used to examine associations between each PNSE and depressive symptoms, adjusting for covariates. Results: Perceived neighborhood safety, social cohesion, and contentedness were negatively related to depressive symptoms (β = −1.14, β = −0.59, and β = −1.46, respectively, all p < 0.001). Similar patterns of negative associations were observed by gender, whereas race/ethnicity-specific analyses revealed the complexity of the associations. Conclusion: As adolescents’ favorable perceptions of their neighborhoods (safety, social cohesion, and contentedness) were related to lower depressive symptoms, efforts toward improving neighborhood conditions and resources may be imperative to drive health equity in specific subgroups and address disparities in the adolescent mental health epidemic.